1999
DOI: 10.1046/j.1365-2141.1999.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Distinct patterns of apoptosis in association with modulation of CD44 induced by thrombopoietin and granulocyte‐colony stimulating factor during ex vivo expansion of human cord blood CD34+ cells

Abstract: Summary. The insuf®cient number of haemopoietic stem cells (HSCs) in cord blood (CB) is the major potential limitation to widespread use of CB for marrow replacement. Cytokine-mediated ex vivo expansion has been proposed as a means of increasing the number of CB HSCs for transplantation. However, the biology of CB HSCs during cytokinemediated ex vivo expansion, such as apoptosis or expression of adhesion molecules, has not yet been elucidated. We have investigated the patterns of apoptosis and CD44 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
4
23
0
Order By: Relevance
“…For example, while TPO induces apoptosis with down-regulation of CD44 in CD34 + UCB cells, FL does not. 16 In contrast, the continuous presence of TPO in stromal cultures resulted in generation of both short-and long-term in vivo repopulating HSC. 17 In the…”
Section: Discussionmentioning
confidence: 99%
“…For example, while TPO induces apoptosis with down-regulation of CD44 in CD34 + UCB cells, FL does not. 16 In contrast, the continuous presence of TPO in stromal cultures resulted in generation of both short-and long-term in vivo repopulating HSC. 17 In the…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts to expand stem cells in vitro have also emphasized the role of the early acting cytokines FL, TPO, SCF and IL6 in regulation of HSPC growth and survival. [8][9][10][11][45][46][47] Using combinations of these cytokines, we observed synergistic effects in support of early progenitors for extended periods of 10 weeks if at least FL + TPO were included. While we observed that the use of cytokines alone expanded early progenitors, and the use of stroma alone decreased their numbers, the combination of stroma and cytokines greatly increased the maintenance and production of HSPC in our ELTC.…”
Section: Discussionmentioning
confidence: 99%
“…27,34 Hyaluronan provides an emergency matrix for tumor cells that have lost attachment to a basal lamina, cells that would otherwise undergo apoptosis. [35][36][37][38][39] Hyaluronan also protects cells from immune surveillance and from immune-mediated cytotoxic agents. 40,41 Hyaluronan is taken up by cells, 42,43 and cancer cells take up more hyaluronan than do normal cells.…”
Section: Discussionmentioning
confidence: 99%